Direct & indirect (a book teaching "How to conversate") - Yaseen, ghulam (Nawab sons publication; Rawalpindi)
"Direct & Indirect: A Book Teaching 'How to Conversate'" provides practical guidance on mastering both direct and indirect communication styles to enhance effective and nuanced conversations.